Standardization of ficus deltoidea jack and orthosiphon stamineus benth for selected anti-hypertensive and anti-angiogenic effects - Darestani, Armaghan Shafaei (2012)
Ficus deltoidea (FD) and Orthosiphon stamineus (OS) were used traditionally for treatment of a wide range of diseases related to diabetes, hypertension, inflammation and angiogenesis related diseases in Malaysia. Therefore, this study was aimed to generate data and evidence about standardization of two medicinal plants namely Ficus deltoidea (FD) and Orthosiphon stamineus (OS) for antihypertensive and anti-angiogenesic effects, since there is lack of sufficient scientific data in this regard. In this study, gravimetric analysis and microbial limit test (MLT) were applied on the dried powder of the leaves to examine the quality and safety of the raw material.